History will teach us nothing? Evolution of the copyright framework for educational uses - Klafkowska-Waśniowska, Katarzyna (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2020)
This article contributes to joins the discussion on the copyright framework for educational uses, focusing on the analysis of Article 27 of the Polish Copyright Act, Article 5 of the Directive on copyright and related rights in the Digital Single Market, and Article. 10 of the Berne Convention. Polish copyright law, the Berne Convention and EU Directives are analysed from the historical perspective to answer the question of whether the legal framework for limitations and exceptions for educational uses has changed to respond adequately to the needs of modern education. The concept of ‘illustration for teaching’ is critically analysed, leading to the conclusion that it reflects narrow approach which fails to address pupils/ students’ activities sufficiently. The objective of the article is to emphasize that modern education needs a flexible approach to educational activities with the use of works. It is emphasized, that the objectives of education and copyright are converging, particularly in the area of the conscious use and adequate description of the source of information.